Evaluation of a novel saliva‐based epidermal growth factor receptor mutation detection for lung cancer: A pilot study. Issue 4 (13th May 2016) - Pu, Dan; Liang, Hao; Wei, Fang; Akin, David; Feng, Ziding; Yan, QingXiang; Li, Yin; Zhen, Yan; Xu, Lin; Dong, Gaochao; Wan, Huajing; Dong, Jingsi; et al.
Abstract : Background: This article describes a pilot study evaluating a novel liquid biopsy system for non‐small cell lung cancer (NSCLC) patients. The electric field‐induced release and measurement (EFIRM) method utilizes an electrochemical biosensor for detecting oncogenic mutations in biofluids. Methods: Saliva and plasma of 17 patients were collected from three cancer centers prior to and after surgical resection. The EFIRM method was then applied to the collected samples to assay for exon 19 deletion and p.L858 mutations. EFIRM results were compared with cobas results of exon 19 deletion and p.L858 mutation detection in cancer tissues. Results: The EFIRM method was found to detect exon 19 deletion with an area under the curve (AUC) of 1.0 in both saliva and plasma samples in lung cancer patients. For L858R mutation detection, the AUC of saliva was 1.0, while the AUC of plasma was 0.98. Strong correlations were also found between presurgery and post‐surgery samples for both saliva (0.86 for exon 19 and 0.98 for L858R) and plasma (0.73 for exon 19 and 0.94 for L858R). Conclusion: Our study demonstrates the feasibility of utilizing EFIRM to rapidly, non‐invasively, and conveniently detect epidermal growth factor receptor mutations in the saliva of patients with NSCLC, with results corresponding perfectly with the results of cobas tissue genotyping.